A Randomized Clinical Trial of Fecal Microbiota Transplant for Alcohol Use Disorder. Issue 5 (16th March 2021) - Bajaj, Jasmohan S.; Gavis, Edith A.; Fagan, Andrew; Wade, James B.; Thacker, Leroy R.; Fuchs, Michael; Patel, Samarth; Davis, Brian; Meador, Jill; Puri, Puneet; Sikaroodi, Masoumeh; Gillevet, Patrick M.
Abstract : Background and Aims: Alcohol use disorder (AUD) is associated with microbial alterations that worsen with cirrhosis. Fecal microbiota transplant (FMT) could be a promising approach. Approach and Results: In this phase 1, double‐blind, randomized clinical trial, patients with AUD‐related cirrhosis with problem drinking (AUDIT‐10 > 8) were randomized 1:1 into receiving one placebo or FMT enema from a donor enriched in Lachnospiraceae and Ruminococcaceae . Six‐month safety was the primary outcome. Alcohol craving questionnaire, alcohol consumption (urinary ethylglucuronide/creatinine), quality of life, cognition, serum IL‐6 and lipopolysaccharide‐binding protein, plasma/stool short‐chain fatty acids (SCFAs), and stool microbiota were tested at baseline and day 15. A 6‐month follow‐up with serious adverse event (SAE) analysis was performed. Twenty patients with AUD‐related cirrhosis (65 ± 6.4 years, all men, Model for End‐Stage Liver Disease 8.9 ± 2.7) with similar demographics, cirrhosis, and AUD severity were included. Craving reduced significantly in 90% of FMT versus 30% in placebo at day 15 ( P  = 0.02) with lower urinary ethylglucuronide/creatinine ( P  = 0.03) and improved cognition and psychosocial quality of life. There was reduction in serum IL‐6 and lipopolysaccharide‐binding protein and increased butyrate/isobutyrate compared with baseline in FMT but not placebo. Microbial diversity increased with higher Ruminococcaceae and other SCFAs, producing taxa following FMT but not placebo, which were linked with SCFA levels. At 6 months, patients with any SAEs (8 vs. 2, P  = 0.02), AUD‐related SAEs (7 vs. 1, P  = 0.02), and SAEs/patient (median [interquartile range], 1.5 [1.25] vs. 0 [0.25] in FMT, P  = 0.02) were higher in placebo versus FMT. Conclusions: This phase 1 trial shows that FMT is safe and associated with short‐term reduction in alcohol craving and consumption with favorable microbial changes versus placebo in patients with alcohol‐associated cirrhosis with alcohol misuse. There was also a reduction in AUD‐related events over 6 months in patients assigned to FMT.